DIVERSITY OF β-GLUCURONIDASE AMONG THE MICROBIOME OF HEALTHY INDIVIDUALS AND PCOS PATIENTS - MUCCEE , F; RAZZAQ , F; IQBAL , R; RAFIQUE , F; AMJAD , A; NASIR , QUA (Biological and Clinical Sciences Research Journal, 2023)
PCOS is a heterogeneous disorder caused by reproductive and immuno-metabolic abnormalities. It is accompanied by dysbiosis of the human gut microbial community. Bacterial enzyme β-glucuronidase (GUSB) performs deglucuronidation of conjugated estrogen, resulting in abnormal conc. of this hormone in females and PCOS incidence. Present study was initiated to characterize the GUSB enzyme in bacteria associated with the gut of healthy and PCOS individuals. Enzyme sequences from ten bacteria were retrieved from the UniProt database and characterized by CELLO, Protparam, SOPMA, AlphaFold, and HDOCK tools. Analysis revealed the localization of enzymes in periplasm and cytoplasm in most bacteria and, in addition to this, the outer membrane only in B. intestinalis. PCOS-associated enzymes were alkaline, with high thermostability and in-vitro stability compared to healthy gut bacterial enzymes. Secondary (2D) and tertiary (3D) structures were comparable in enzymes of both these groups. The affinity of GUSB was higher for catechin in PCOS-associated bacteria than bacteria found in a healthy gut. Hence, catechin can be an effective ligand for inhibiting the GUSB enzyme in PCOS patients.